Global Monitoring Report, 2011 : Improving the Odds of Achieving the MDGs. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2011)
With less than five years left to achieve the MDGs, this year's report looks at the prospects and challenges for reaching the goals. It also examines the great diversity of performance across indicators, countries, and categories of countriesto determine the necessary policies to fill the remaining gaps.